Collective action initiatives to improve marketing performance: Lessons from farmer groups in Tanzania - Barham, James; Chitemi, Clarence (International Food Policy Research Institute, 2008)
The primary inquiry of this study is to identify and understand the underlying factors that enable smallholder farmer groups to improve their market situation. The specific objective of this paper is to examine to what extent certain group characteristics and asset endowments facilitate collective action initiatives to improve group marketing performance. This objective is approached through an evaluation of a government-led program in Tanzania, which is attempting to increase smallholder farmers' incomes and food security through a market-oriented intervention. Findings suggest that more mature groups with strong internal institutions, functioning group activities, and a good asset base of natural capital are more likely to improve their market situation. Gender composition of groups also factors in group marketing performance. It acts as an enabling factor for male-dominated groups and as a disabling factor for female-only groups. Structural social capital in the form of membership in other groups and ties to external service providers, and cognitive social capital in the form of intragroup trust and altruistic behavior are not significant factors in a group's ability to improve its market situation.